Transformasi Strategis SDM untuk Keberlanjutan Perusahaan di Era Industri 4.0: Studi Kasus PT XYZ - Federova, Callista; Handayani, Kristin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
The Fourth Industrial Revolution era has brought a significant influence on changing the digital business landscape, including in the banking sector. The position of employees as individual human resources (HR) who present knowledge, skills, and professional service capabilities is seriously threatened at a time when digital change and complexity is said to be able to replace all human work. The strategic transformation of human resource management (HR) is inevitably crucial at PT. XYZ to ensure the sustainability of the banking business. This research aims to explain the strategic role of human resource management development in PT. XYZ in facing the complexity of digital technology transformation in banking. The method used is a qualitative approach, through interviews, observations and documentation. The object of the study is Bank XYZ employees who graduated from the Management Development Program (MDP) including the Director of Retail Banking, Head of Networking and Distribution, and Staff XYZ. Data analysis through stages, data reduction, data presentation and ending with drawing conclusions. The results of the study show that the strategic transformation in human resource management (HR) carried out by PT. XYZ to remain relevant in the industrial era 4.0. Employees remain recognized as a key factor in building customer trust, through their expertise in utilizing technology. For this reason, integration between employees and technology is crucial to increase the effectiveness and sustainability of the company. This study recommends the implementation of an updated training program for mastering the latest technology. Another suggestion is the need to strengthen the core values of the organization, such as integrity, discipline, and employee concern for customers. Employees should also remain open to change and commit to learning new things